THE STYLISTIC DEVICES IN THE PROSAIC WORKS BY CHARLES DICKENS - Abdurazzoqova Kamola (Ustozlar uchun, 2025)
Charles Dickens is renowned for his vivid storytelling and memorable characters, but his mastery of stylistic devices is equally significant in shaping his narratives. This article explores various stylistic devices employed by Dickens in his prosaic works, particularly focusing on their roles in character development, thematic expression, and reader engagement.